EVALUASI PENGGUNAAN OBAT DIABETES MELITUS PADA PASIEN PSIKIATRI DI RUMAH SAKIT JIWA SAMBANG LIHUM PERIODE 2022-2023 - Saputri, Rina; Maulani, Eka Febrianti; Hidayah, Nur; Aryzki , Saftia (Universitas Borneo Lestari, 2025)
Mental disorders are severe mental health problems that cause cognitive, affective and social functioning impairments. Diabetes mellitus is a disease with hyperglycemia. The use of diabetes mellitus drugs in psychiatric patients can pose a risk of potential interactions between drugs that will result in the possibility of irrational drug use. The purpose of this study was to evaluate the use of diabetes mellitus drugs in psychiatric patients at Sambang Lihum Mental Hospital. The method used is descriptive observational method with survey design and sampling technique, namely total sampling and retrospective data collection with appropriate assessment indicators are the 14 appropriate criteria from the Ministry of Health, so that the results obtained are the majority of gender is male as many as 15 people (55.56%) and the majority of age is 45-59 years as many as 16 people (59.26%). Evaluation of the use of single diabetes mellitus drugs as many as 9 people (33.33%) and a combination of 18 people (66.67%). Evaluation of the use of diabetes mellitus drugs was obtained by 26 rational people (96.30%) and 1 irrational person (3.70%) and all the use of diabetes mellitus drugs was in accordance with the hospital formulary and treatment guidelines. The conclusion of this study is that there is still irrational use of drugs in the criteria of patient adherence to treatment so that it has the potential to cause harm to the patient.